Feasibility of Combined Unipolar and Bipolar Voltage Maps to Improve Sensitivity of Endomyocardial Biopsy. (June 2015) - Casella, Michela; Pizzamiglio, Francesca; Dello Russo, Antonio; Carbucicchio, Corrado; Al-Mohani, Ghaliah; Russo, Eleonora; Notarstefano, Pasquale; Pieroni, Maurizio; D'Amati, Giulia; Sommariva, Elena; Giovannardi, Marta; Carnevali, Andrea; et al.
Abstract : Background—: Endomyocardial biopsy (EMB) has a low sensitivity. Electroanatomic voltage mapping (EVM) is effective in guiding EMB thanks to its ability in identifying and locating low-voltage regions. The analysis of unipolar EVM can correlate with epicardial pathological involvement. We evaluated the unipolar EVM in EMB areas to determine whether it can increase EMB sensitivity in diagnosing epicardial diseases. Methods and Results—: We performed endocardial bipolar EVM-guided EMBs in 29 patients and we analyzed unipolar EVM at withdrawal sites. Eighty myocardial samples were collected (mean, 2.8±0.9; median, 3 fragments per patient) and 60 were suitable for histological analysis. Ten specimens (17%) were collected from an area with discordant normal bipolar/low-voltage unipolar EVM and they were diagnostic or suggestive for arrhythmogenic right ventricular dysplasia/cardiomyopathy in 6 patients, for myocarditis and sarcoidosis in 1 patient each. Six samples (10%) were collected from an area with discordant low-voltage bipolar/normal unipolar EVM and they showed nonspecific features. The sensitivity of unipolar EVMs for a diagnostic biopsy finding EMB was significantly higher compared with bipolar EVMs analyzed according to samples ( P <0.01) and patients ( P =0.008). The specificity of unipolar EMB was better than bipolar EMB when analyzed for all samples ( P =0.0014) but the difference did not reach statistical significance when analyzed by patient ( P =0.083). The diagnostic yield was 63.3% for the bipolar and 83.3% for the unipolar EVM. Conclusions—: These findings suggest that use of a combined bipolar/unipolar map may be able to improve the diagnostic yield of endomyocardial ventricular biopsy. Abstract : Supplemental Digital Content is available in the text.